Pemodelan Sistem Pemilihan Tempat POI Terdekat di Wilayah Klaten Kota Menggunakan Metode Dijkstra oleh PT. Telkom Klaten - Kusumawati, Erlina Kumala; Hartanti, Dwi; Santosa, Tri Djoko (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The Point of Interest (POI) represents a specific geographic location defined by its coordinates, including longitude and latitude, and holds value as a site of interest or utility. Examples of POIs include tourist attractions, hotels, restaurants, ATMs, pharmacies, health centers, retail shops, gas stations, and other categories integral to modern navigation systems. PT. Telkom Klaten has faced increased demands to conduct POI surveys efficiently, driven by advancements in technology that call for faster and more streamlined processes. A primary challenge in these surveys is the selection of an optimal route that minimizes time, costs, and fuel consumption, given that the company currently relies on manual input in Google Maps to determine distance and travel time. This manual approach may hinder survey efficiency and increase operational costs. To address this, an application employing the Dijkstra algorithm was developed to determine the shortest route effectively. The Dijkstra algorithm, known for selecting edges with minimal weight to connect sequential nodes, requires defined origin and destination points, thereby generating the most efficient route between them. This study applies the Dijkstra algorithm to optimize survey routes by modeling them as graph-based routes, aiming to identify the shortest and most efficient paths between multiple POI locations. The findings indicate that the Dijkstra algorithm significantly reduces travel distance and time, thereby achieving notable savings in fuel and operational time for POI surveys.